ANALISIS MUATAN MATERI BAB XIV KOMPILASI HUKUM ISLAM PASAL 100 TENTANG PEMELIHARAAN ANAK DAN PUTUSAN MAHKAMAH KONSTITUSI R.I. NOMOR 46/PUU-VIII/2010 - Zuhriah, Erfaniah; Mayasari, Lutfiana Dwi (Fakultas Syariah, 2012)
Constitutional Court’s decision on the rights of children who were born out of wedlock causes various controversies. On the one hand, it is considered as a positive decision for children’s benefit and their future. On the other hand, it is considered also as a negative decision by legalizing unregistered marriage. Using a field research and qualitative approach, this research produces a conclusion that four of respondents from different background of organizations agree with this constitutional court decision if the intended object is the children from Sirri (unregistered) marriage. Furthermore, one respondent agrees if this decision becomes a guideline and no longer a phenomenon. The most important message from informants is a recommendation that Constitutional Court not to issue another ambiguous fatwa and this institution is capable to make a humanist decision and remains in the corridors of the religious demands that have been rooted in the community. Keputusan mahkamah konstitusi tentang hak anak diluar nikah menimbulkan berbagai macam kontroversi. disatu pihak keputusan tersebut dianggap positif untuk kemaslahatan anak dan masa depan mereka, dan di lain pihak keputusan tersebut dianggap negative karena melegalkan pernikahan dibawah tangan. Dalam penelitian yang menggunakan jenis penelitian field research dengan pendekatan kualitatif ini menghasilkan suatu kesimpulan bahwa empat responden dengan latar belakang organisasi yang berbeda menyatakan setuju dengan keputusan MK tersebut jika yang dimaksud adalah anak hasil pernikahan sirri. Dan satu responden menyatakan setuju jika keputusan tersebut menjadi sebuah pedoman bukan lagi fenomenal. Pesan terpenting dari para informan adalah himbauan agar MK tak lagi mengeluarkan suatu fatwa yang ambigu dan mampu menciptakan keputusan yang humanis dan tetap dalam koridor tuntutan keagamaan yang telah mengakar di masyarakat.